(untitled) (International Journal of Food and Nutritional Sciences, 2022)
G Protein-Coupled Receptors (GPCRs) constitute a large and diverse family of cell surface receptors that play a crucial role in transducing extracellular signals into intracellular responses. This manuscript aims to provide a comprehensive overview of GPCRs, exploring their structure, signaling pathways, physiological functions, and their significance as therapeutic targets. Understanding the intricate mechanisms underlying GPCR signaling is essential for the development of novel pharmacological interventions in various diseases.